Clinical Spectrum of Tauopathies - Olfati, Nahid; Shoeibi, Ali; Litvan, Irene (Frontiers in Neurology, 2022)
Tauopathies are both clinically and pathologically heterogenous group of disorders characterized by neuronal and/or glial accumulation of misfolded tau protein. It is now well understood that every pathologic tauopathy may present with various clinical phenotypes based on the primary site of involvement and the spread and distribution of the pathology in the nervous system making clinicopathological correlation more and more challenging. Clinical spectrum of tauopathies includes syndromes with strong association with an underlying primary tauopathy, including Richardson syndrome (RS), corticobasal syndrome (CBS), non-fluent, agrammatic primary progressive aphasia (nfa-PPA) / apraxia of speech, pure akinesia with gait freezing (PAGF), and behavioral variant frontotemporal dementia (bvFTD), or weak association with an underlying primary tauopathy, including Parkinsonian syndrome, late onset cerebellar ataxia, primary lateral sclerosis, semantic variant PPA (svPPA), and amnestic syndrome. Here we discuss clinical syndromes associated with various primary tauopathies and their distinguishing clinical features as well as new biomarkers becoming available to improve in vivo diagnosis. Although the typical phenotypic clinical presentations lead us to suspect specific underlying pathologies, it is still challenging to differentiate pathology accurately based on clinical findings due to large phenotypic overlaps. Larger pathology-confirmed studies to validate use of different biomarkers and prospective longitudinal cohorts evaluating detailed clinical, biofluid, and imaging protocols in subjects presenting with heterogenous phenotypes reflecting a variety of suspected underlying pathologies are fundamental to better understanding of the clinicopathological correlations.